E-learning in higher education: academic factors for student permanence - Seabra, Filipa (2018)
E-learning has increasingly been acknowledged as a legitimate option which contributes to the democratization of higher education. One of its advantages is the possibility of reaching non-conventional publics for higher education, including workers, adults, and people who live outside the main city centers. This is also an important aspect with regard to sustainability education, particularly when addressing climate change education, as these publics may be less easily reached by conventional educational settings. Permanence is a key issue and a significant obstacle to the success of any e-learning based initiative—in order for the educational goals to be met, one must ensure, in the first place, that students who enroll in a program are able to persevere, successfully learn, and reach graduation. This chapter presents a framework of the concept of permanence in higher education, particularly in e-learning contexts and concerning adult populations. It presents an empirical research concerning the academic factors related to good permanence outcomes. Data were gathered using a survey by questionnaire answered by students of an undergraduate degree developed through e-learning in a Portuguese public university.